2019
DOI: 10.1039/c9ra03662h
|View full text |Cite
|
Sign up to set email alerts
|

Size dependent anti-invasiveness of silver nanoparticles in lung cancer cells

Abstract: Size-dependent anti-invasiveness effect of AgNPs was determined using A549 lung adenocarcinoma cells. The 13 nm AgNPs can significantly inhibit the migration and invasion of A549 cells and induce the elevated level of ROS and NF-κB directed cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Many researchers emphasize on cytotoxicity of the metal NPs and highlight the migration of tumor cell and metastasis-related ability may be impacted by nanomaterials 78 . Herein, the strong inhibition efficacy of AgNPs on migration was observed in cancer cells, which were in line with other group 79 , 80 . Thus, this suggests that silver nanoparticles may have potential function in the inhibition of the metastasis.…”
Section: Resultssupporting
confidence: 88%
“…Many researchers emphasize on cytotoxicity of the metal NPs and highlight the migration of tumor cell and metastasis-related ability may be impacted by nanomaterials 78 . Herein, the strong inhibition efficacy of AgNPs on migration was observed in cancer cells, which were in line with other group 79 , 80 . Thus, this suggests that silver nanoparticles may have potential function in the inhibition of the metastasis.…”
Section: Resultssupporting
confidence: 88%
“…The inhibitive effect of AgNPs decrease with the increase of their particle size and reversible for concentration. 65,66 In our study, as compared to CMBC-EDA/CHO-PECTIN, CMBC-EDA/CHO-PECTIN/AgNPs showed higher A549 cell proliferation and migration during the wound healing process (Figure 10). The wound healing in A549 cells might be due to the inductive effect of the synthesized film or the absence of inhibitory effect in AgNPs due to particle size and concentration.…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…AgNPs (13 nm) caused a decrease in the anti-apoptotic protein Bcl-2 and an increase in the pro-apoptotic protein Bax and upregulated the phosphorylation of NF-κB in A549 cells, indicating that AgNPs (13 nm) induced apoptosis via the NF-κB pathway. However, large AgNPs (45 and 92 nm) did not activate the apoptosis signaling pathway [166]. The size of silica NPs (19, 43, 68 nm) is negatively correlated with the apoptosis and necrosis rates of HepG2 cells [61].…”
Section: The Impact Of Np Physicochemical Properties On Apoptosismentioning
confidence: 95%